BENTUK-BENTUK PERILAKU MENYIMPANG SEKS BEBAS DIKALANGAN MAHASISWA (Studi Kasus Mahasiswa Yang Tinggal di Kelurahan Simpang Baru) - Eko Rinfa; Indrawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Intercourse Students come from backgrounds different course will produce a pattern of behavior that is interesting to observe. Students who live outside the main neighborhood with a different oversight by students who live on the main environmental or family environment. In a family environment, parents provide guidance and role models students in attitude and provide instruction in the norms prevailing in society. Parents will give warning if the juvenile or the child they violate these norms. Unlike the students who live not on the main environment. Modeling and guidance they get from colleagues who are also students who are still in developmental stages. The research method is a way to collect data and facts. This type of research is qualitative descriptive. A qualitative approach describe, express, tell and summarize a variety of conditions and circumstances. Subject study researchers examined the problem of deviant behavior of students took place in the village area of the new intersection exactly in the way heron magic. Mechanical determination of informants used in this study using Snow Ball Sampling. Data used primary data and secondary data, techniques and means of collecting data by interview, observation and documentation. The results showed that 1). The forms of sex behavior by students in the village of Simpang Baru showed a majority of informants were not able to abstinence while being with his girlfriend so they have sex without thinking of their official status. 2). Factors that lead students in the village of Simpang Baru promiscuous form: Internal factors are factors that come from within the student. Where such troubled students cannot make adjustments with the surrounding environment such as social norms that exist in society. External factor occurs due to the dominant environmental conditions experienced by these students, the lack of economic stress in families and the stigma.Keywords: Behavior, Free Sex, Student.